Search for direct pair production of supersymmetric top quarks decaying to all-hadronic final states in pp collisions at root s=8 TeV - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Ero,J; Flechl,M; Friedl,M; et al. (European Physical Journal C: Particles and Fields, 2016)
Results are reported from a search for the pairproduction of top squarks, the supersymmetric partners oftop quarks, in final states with jets and missing transversemomentum. The data sample used in this search was collectedby the CMS detector and corresponds to an integrated luminosityof 18.9 fb−1 of proton-proton collisions at a centreof-massenergy of 8 TeV produced by the LHC. The searchfeatures novel background suppression and prediction methods,including a dedicated top quark pair reconstruction algorithm.The data are found to be in agreement with the predictedbackgrounds. Exclusion limits are set in simplifiedsupersymmetry models with the top squark decaying to jetsand an undetected neutralino, either through a top quark orthrough a bottom quark and chargino. Models with the topsquark decaying via a top quark are excluded for top squarkmasses up to 755 GeV in the case of neutralino masses below200 GeV. For decays via a chargino, top squark masses upto 620 GeV are excluded, depending on the masses of thechargino and neutralino.